Ecosystem service delivery in Karst landscapes: anthropogenic perturbation and recovery - Quine, Timothy; Guo, Dali; Green, Sophie M.; Tu, Chenglong; Hartley, Iain; Zhang, Xinyu; Dungait, Jennifer; Wen, Xuefa; Song, Zhaoliang; Liu, Hongyan; Buss, Heather; Barrows, Timothy; et al. (Springer, 2017)
Covering extensive parts of China, Karst landscapes are exceptional because rapid and intensive land use change has caused severe ecosystem degradation within only the last 50 years. The twentieth century intensification in food production through agriculture has led to a rapid deterioration of soil quality, evidenced in reduced crop production and rapid loss of soil. In many areas, a tipping point appears to have been passed as basement rock is exposed and ‘rocky desertification’ dominates. Through the establishment of the “Soil processes and ecological services in the karst critical zone of SW China” (SPECTRA) Critical Zone Observatory (CZO) we will endevaour to understand the fundmental processes involved in soil production and erosion, and investigate the integrated geophysical-geochemical-ecological responses of the CZ to perturbations. The CZ spans a gradient from undisturbed natural vegetation through human perturbed landscapes. We seek to understand the importance of heterogeneity in surface and below-ground morphology and flow pathways in determining the spatial distribution of key stocks (soil, C, vegetation, etc.) and their control on ecosystem service delivery. We will assess the extent to which the highly heterogeneous critical zone resources can be restored to enable sustainable delivery of ecosystem services. This paper presents the CZO design and initial assessment of soil and soil organic carbon stocks and evidence for their stability based on caesium-137 (137Cs) data.
Keywords: Soil degradation; Ecosystem services; Caesium-137; Karst, China